Improvement Photocatalytic Activity of Ag2S Nanoparticles by Gold Doping - Baeissa, E.S. (Asian Journal of Chemistry, 2014)
Hydrothermal method was used to prepare Ag2S nanoparticles, photoassisted deposition method was used to doped gold into Ag2S nanoparticles. The obtained nanoparticles are characterized by X-ray photoelectron spectroscopy, photoluminescence emission spectra, ultraviolet and visible spectroscopy, surface area measurement, X-ray diffraction and transmission electron microscopy. The photocatalytic removal of cyanide under visible light was used to measure photocatalytic performance of Ag2S and Au/ Ag2S nanoparticles. The results reveal that doping of gold into Ag2S cause shift absorption of Ag2S to high wavelength as shown in UV-visible spectra. XPS results confirm the presence of gold metal above surface of Ag2S nanoparticles. 0.6 wt % Au/Ag2S nanoparticle has highest photocatalytic activity and is stable after reuse for five times.